Influence of concentrations of a mixtures of 3-indoleacetic acid and boron, and that of stem carbohydrates and nitrogen contents on rooting of “Pueraria phaseoloides" cuttings - Barrueto Cid, L. Pedro; Fialho, Josefino de Freitas; Neves, Maria Amazonilde Cruz (Pesquisa Agropecuaria Brasileira, 2014)
Factors affecting the rooting of the legume Pueraria phaseoloides were investigated. Using cuttings from the lower, middle and upper third of the stems, the effect of four different concentrations of an aqueous mixture of 3-indoleacetic acid (IAA) and boron (B) and that of the soluble carbohydrates and total nitrogen contents in stem segments were determined. The mixture comprising 100 ppm of IAA and 10 ppm of B was the most effective in inducing rooting, especially when applied to cuttings from older parts of the stem. Analysis for the presence of soluble carbohydrates in the different cuttings revealed no differences among them. However, the nitrogen content of the upper third of the stem was significantly higher than those of the other stem segments. An hypothesis is proposed that nitrogen level in stem is more critical than the carbohydrate in influencing the rooting of this legume cover.